DYNAMIC MODULATION OF TWO-DIMENSIONAL ELECTRON GAS AT THE OXIDE HETEROSTRUCTURE WITH EXTERNAL STIMULI - ANSHU GUPTA (My University, 2025)
P. W. Anderson in his noble article quoted “More is different”. His quote highlighted a key aspect of complex systems, indicating that emergent properties arise at different levels of complexity that cannot be easily predicted from the properties of individual components alone. The Dirac equation introduced almost a century ago, unified special relativity and quantum mechanics, predicting helicity, Chern numbers, and Weyl fermions. Its impact extends beyond particle physics to low-dimensional condensed matter physics, facilitated by the fabrication of 2D structures like graphene, enabling the realization of these theoretical constructs. Semiconductor physics has evolved from theoretical to practical applications, particularly in spintronics and quantum devices. Group-IV elements, such as silicon and germanium, have dominated semiconductor physics due to their electrical characteristics and availability. Group III-V alloys, which combine elements like aluminium, gallium, and indium with nitrogen, phosphorus, or arsenic, offer a wider range of electrical characteristics and bandgap engineering possibilities. Artificial heterostructures have been created by layering different semiconductor materials with controlled thicknesses and compositions, enabling the creation of two- dimensional electron gas (2DEG). This discovery has led to the quantum Hall effect (QHE) and fractional quantum Hall effect (FQHE), providing insights into electron behaviour and paving the way for new electronic devices. Transition metal oxides (TMOs) offer unique opportunities for studying physical characteristics due to their spin, lattice, and orbital degrees of freedom, as well as high electron correlations. TMOs are advantageous over semiconductors for spintronic applications due to their ability to integrate various emergent phenomena and exhibit a wide range of electronic, optical, and magnetic properties, including insulating, semiconducting, metallic, superconducting, ferroelectric, pyroelectric, piezoelectric, ferromagnetic, multiferroic, and nonlinear optical effects. Oxides are ideal materials for future electronic devices due to their integrability and other desirable features. In this dissertation, we investigated and researched the heterostructure LaVO 3 (LVO) – KTaO 3 (KTO), which has shown the Rashba effect with the highest spin-orbit coupling strength among oxides heterostructures. The "Rashba effect," or momentum-dependent splitting of spin-bands in an electronic system, has been discovered to play an important role in spintronic devices. Strong spin-orbit coupling is required to realize the Rashba effect. The goal of selecting KTO is its vistrong spin-orbit coupling, in addition to its simple cubic structure and other qualities such as a high dielectric constant, which make it appropriate for future-generation spintronic devices. The heterostructure LVO-KTO produced in our study exhibits unique signatures of the Rashba effect on the angular magnetoresistance while exhibiting negative longitudinal magnetoresistance, planar Hall effect, and anisotropic magnetoresistance. Also, it points to an exciting possibility of using non-magnetic Rashba materials as vector magnetic field detectors. Other than LVO-KTO heterostructure, my work focuses on the modulation of the 2DEG at the interface of oxide heterostructures by using external perturbations as stimuli. By using the light illumination and the electrostatic gating as the stimuli, we have compared the light-matter interaction at the interface of LVO- SrTiO 3 (STO) (110) and LVO-STO (111), which both are polar-polar interfaces. Both interfaces have shown persistent photoconductivity (PPC) may provide a guideline to achieve higher performance in oxide-based memory devices and optical switches. Also, we explored the photoconductive behaviour at the KTO-based interface: LVO- KTO (111) by studying their photo response at 76 K and 300 K. Finally, we fabricated EuO on the KTO substrate, which has been examined as a potential candidate for spintronics and optoelectronic applications. In this work, we have exploited the PPC to realize the neuromorphic behaviour in our system. The EuO-KTO interface acted as an artificial synapse. The biological synapse is the junction between two neurons and its weight or connection strength can be altered precisely depending on the activities of the pre- and post- synaptic neurons. This artificial synapse mimics the behaviour of the biological synapse while showing the transition from short-term memory (STM) to long-term memory (LTM), pulsed pair facilitation (PPF), long-term potentiation (LTP) and long-term depression (LTD), volatile to non- volatile resistive switching. The results presented offer a promising route towards 2DEG formed at oxide heterostructure-based synaptic emulation for neuromorphic computing.
Keywords: OXIDE HETEROSTRUCTURE; ELECTRON GAS